(untitled) (Research, Society and Development, 2025)
The present study aimed to quantify the genetic divergence between bacabi genotypes based on these characters, contributing to the sustainable management and improvement of the species.The species is economically important, known for its production of oil similar to olive oil and its nutritious pulp used in beverages and food products. Despite its potential, its commercialization still depends largely on extractive exploitation. Data were obtained from ten rachillae of each genotype, totaling 220 samples. Twelve quantitative traits were evaluated, such as rachilla length (CR), number of female (NFF) and male (NFM) flowers, as well as measurements related to floral structure. Data were subjected to univariate analysis (ANOVA), followed by the Scott & Knott test (P ≤ 0.05) for grouping of means, and multivariate analyses involving the UPGMA and Tocher methods. The results revealed significant variability for most traits, with NFM (80.43%) and NFF (16.89%) being the largest contributors to genetic divergence. The most divergent pair was G4 and G18 (2.57), while the least divergent was G6 and G9 (0.54). The genotypes formed seven divergent groups using the Tocher method and two main groups using the UPGMA method. Rachila length was the most divergent trait. These results demonstrate significant genetic variability among bacabi genotypes for the evaluated traits, making them essential for planning conservation and genetic improvement strategies.